2016
DOI: 10.1007/s13402-016-0298-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic variation in the lncRNA HOTAIR associated with HPV16-related cervical cancer pathogenesis

Abstract: Our data indicate that rs2366152C not only has the potential to serve as a marker for singling out CaCx cases lacking metastatic molecular signatures, but also to explain the functional inactivation of HOTAIR in these cases, including the mechanism of its down-regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…The initial search yielded 337 publications, 262 of which were excluded for being irrelevant to HOTAIR polymorphisms, by reading titles and abstracts. On further evaluation, 37 articles were either biochemical studies or reviews and were therefore ruled out; 18 articles focused on non-cancer diseases such as rheumatoid arthritis and hearing loss; 1 article explored the relationship between cervical cancer risk and HOTAIR rs2366152 polymorphisms, which were not repeated in other published studies, resulting in the impossibility of data pooling; 22 and 1 article focused on the HOTAIR rs7958904 polymorphisms in lung cancer, but failed to offer detailed genotype information data. 23 Therefore, we enrolled 18 articles of 36 studies in this meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The initial search yielded 337 publications, 262 of which were excluded for being irrelevant to HOTAIR polymorphisms, by reading titles and abstracts. On further evaluation, 37 articles were either biochemical studies or reviews and were therefore ruled out; 18 articles focused on non-cancer diseases such as rheumatoid arthritis and hearing loss; 1 article explored the relationship between cervical cancer risk and HOTAIR rs2366152 polymorphisms, which were not repeated in other published studies, resulting in the impossibility of data pooling; 22 and 1 article focused on the HOTAIR rs7958904 polymorphisms in lung cancer, but failed to offer detailed genotype information data. 23 Therefore, we enrolled 18 articles of 36 studies in this meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…LNMICC promoted lymph node metastasis of CC by recruiting NPM1 (a nuclear factor) to the promoter of FABP5 (a fatty acid binding protein) . Aberrant expression of lncRNA HOTAIR was associated with pathogenesis of HPV16‐related CC . Regarding the present study, a recently‐identified oncogene lncRNA TMPO antisense RNA 1 (TMPO‐AS1), located at chromosome 12q23.1, has attracted attention with respect to cancer therapies.…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, some research on selected SNPs has been completed. The rs2366152C SNP on HOTAIR, for example, affected the secondary structure, with loss of the binding site for miR-22, in herpes virus (HPV)16-related cervical cancer development [76]. A novel risk SNP rs114020893 was predicted to change the secondary structure in the lncRNA NEXN-AS1 at 1p31.1, and may contribute to lung cancer susceptibility [77].…”
Section: Discussionmentioning
confidence: 99%